Experimental Study on Characteristics of CO2 Hydrate Formation in Spray Reactor - An Lihuan; Liu Daoping; Yang Xiaoshu; Yang Liang; Yang Meng (Zhileng xuebao)
Based on water spraying technology, the characteristics of CO2 hydrate formation in spray reactor were investigated experimentally. The effects of temperature and pressure in the reactor, the coolant temperature in entrainment and the use of buffer tank on CO2 hydrate formation characteristics were studied. Compared with CO2 hydrate formation under static conditions, the pressure drop in the spraying process was larger, and CO2 hydrate was formed much faster. The water was sprayed into gas, providing much more gas-water contact surface. The experimental results showed that the duration of CO2 hydrate formation was about 20 minutes in the presence of a buffer tank. However, under the same working condition, the duration of CO2 hydrate formation was about 40 minutes without a buffer tank. The buffer tank sent CO2 into the spraying system evenly and stably, which enhanced the spraying effect and doubled the CO2 hydrate formation rate. The experimental results provide an important reference for the analysis of CO2 hydrate formation and engineering applications.